Perinatal exposure to ultraprocessed foods and its impact on maternal gut dysbiosis, placental inflammation, and neonatal immune programming: A systematic review - I Nyoman Hariyasa Sanjaya; Wiku Andonotopo; Muhammad Adrianes Bachnas; Julian Dewantiningrum; Mochammad Besari Adi Pramono; Ryan Saktika Mulyana; Evert Solomon Pangkahila; Muhammad Ilham Aldika Akbar; Cut Meurah Yeni; Dudy Aldiansyah; Nuswil Bernolian; Anak Agung Gede Putra Wiradnyana; Adhi Pribadi; Sri Sulistyowati; Milan Stanojevic; Asim Kurjak (Majalah Obstetri & Ginekologi, 2025)
HIGHLIGHTS Perinatal ultraprocessed food (UPF) exposure disrupts maternal gut microbiota composition, increasing pro‑inflammatory taxa and systemic endotoxemia. Placental immune activation and oxidative stress represent key mediators linking maternal diet to fetal immune and metabolic programming. Neonatal outcomes include altered regulatory T‑cell development, Th2 immune skewing, allergic sensitization, and early metabolic risk. Integrated dietary counseling, microbiota‑targeted interventions, and public health policies are urgently needed to mitigate transgenerational immune health risks.   ABSTRACT Objective: To synthesize and critically evaluate evidence linking perinatal exposure to ultraprocessed foods (UPFs) with maternal gut dysbiosis, placental inflammation, and neonatal immune programming, and to identify translational implications for perinatal care. Materials and Methods: A systematic narrative review was conducted following PRISMA 2020 guidelines, without PROSPERO registration. Literature searches of major databases (2000–March 2025) identified 1,845 records. After screening and eligibility assessment, 20 studies were included. Study quality was appraised using validated tools, and data were synthesized thematically into evidence domains covering maternal microbiota, inflammatory pathways, placental changes, and neonatal immune outcomes. Results: Maternal UPF consumption was associated with gut dysbiosis characterized by reduced microbial diversity, increased pro-inflammatory taxa, and systemic endotoxemia. Elevated inflammatory biomarkers including lipopolysaccharide, interleukin‑6, tumor necrosis factor‑a, and C‑reactive protein were frequently reported. Limited placental studies revealed increased innate immune activation and oxidative stress. Neonatal immune alterations included regulatory T cell suppression, T helper 2 skewing, increased allergic sensitization, and metabolic programming changes. Evidence strength was highest for maternal gut dysbiosis and immune programming but limited for direct placental mechanisms. Translational opportunities include dietary counseling, microbiota-targeted interventions, and public health strategies aimed at improving maternal diet quality. Conclusion: Perinatal exposure to UPFs adversely impacts the maternal gut–placenta–fetal immune axis. Integrated dietary interventions and population-level nutrition policies are urgently needed to mitigate downstream transgenerational immune risk.